Paraphilic Interests Versus Behaviors: Factors that Distinguish Individuals Who Act on Paraphilic Interests From Individuals Who Refrain. (June 2023) - Molen, Lauryn Vander; Ronis, Scott T.; Benoit, Aryn A.
Little is known about distinct factors linked with acting on paraphilic interests or refraining from engaging in paraphilic behaviors. Participants from Canada and the United States ( N = 744), aged 19–42 years ( M = 29.2; SD = 3.18), were recruited through Amazon's Mechanical Turk. Participants completed questionnaires about their paraphilic interests and behaviors, as well as potential key factors linked to behavioral engagement (i.e., perceptions of consent, sexual excitation/inhibition, impulsivity, moral disengagement, empathy). Results indicated that higher moral disengagement and impulsivity, lower sexual control (i.e., high sexual excitation, low sexual inhibition), and maladaptive understandings of consent were best able to differentiate individuals who reported highly stigmatized (e.g., hebephilia, pedophilia, coprophilia) or Bondage and Dicipline, Dominance and Submission, Sadism and Masochism(BDSM)/Fetish paraphilic interests and engagement in the paraphilic behaviours associated with these interests relative to individuals who did not report such paraphilic interests or behaviors. Moreover, higher moral disengagement, impulsivity, and maladaptive perceptions of consent were best able to differentiate non-consensual paraphilic interests and behaviours (e.g., voyeurism, exhibitionism) compared to individuals who did not report these paraphilic interests or behaviours. These results provide future directions for the exploration of mechanisms that may contribute to engagement in paraphilic behaviors and may be targets for intervention aimed at preventing engagement in potentially harmful paraphilias.